2010
DOI: 10.22230/jripe.2010v1n2a22
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Relationships in the Field of Obesity: Data from Canada

Abstract: Background: While it is generally acknowledged that an interprofessional approach is necessary to treat and prevent obesity, there have been few empirical studies examining the working relationships of professionals in the obesity field.Methods: In this article social network analysis is used to examine the working relationships of 111 attendees, representing eleven different health professions, at the first National Obesity Summit in Canada. We assessed the extent of engagement in interprofessional relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Lastly, this study also identified the influence of disparities in health and healthcare as significant barriers to the achievement of better health outcomes via IPCP. Although there is ample literature on the topic of social capital and its link to health disparities from outside the realm of interprofessional care (Berkman & Glass, 2000;Bourdieu, 1986;Islam et al, 2006;Macinko & Starfield, 2001), as well as editorials (Soubhi, 2010) and deductive empirical studies (Godley et al, 2011;Godley & Russell-Mayhew, 2010) that measured social capital in the context of interprofessional care, no prior inductive research studies specific to this phenomenon and to the context of the lives of disadvantaged populations in the US had been identified (Y. Jadotte et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, this study also identified the influence of disparities in health and healthcare as significant barriers to the achievement of better health outcomes via IPCP. Although there is ample literature on the topic of social capital and its link to health disparities from outside the realm of interprofessional care (Berkman & Glass, 2000;Bourdieu, 1986;Islam et al, 2006;Macinko & Starfield, 2001), as well as editorials (Soubhi, 2010) and deductive empirical studies (Godley et al, 2011;Godley & Russell-Mayhew, 2010) that measured social capital in the context of interprofessional care, no prior inductive research studies specific to this phenomenon and to the context of the lives of disadvantaged populations in the US had been identified (Y. Jadotte et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Social capital, which consists of the sum of the cognitive and structural or interpersonal linkages that connect people together (Islam, Merlo, Kawachi, Lindstrom, & Gerdtham, 2006), has been proposed as a possible theoretical framework by which IPL acts to enhance IPCP (Gloede, Hammer, Ommen, Ernstmann, & Pfaff, 2013;Godley & Russell-Mayhew, 2010) and thereby potentially improve patient health outcomes. However, this proposed mechanism has not been demonstrated inductively or grounded in any empirical qualitative study to date.…”
Section: Implications For Interprofessional Practicementioning
confidence: 99%
See 2 more Smart Citations
“…While many studies have devised measures of interprofessionalism at the individual or team level (Archibald, Trumpower, & MacDonald, 2014;Chiu, 2014;Dominguez, Fike, MacLaughlin, & Zorek, 2015;Dougherty, 2016;Dow, DiazGranados, Mazmanian, & Retchin, 2014;Fike et al, 2013;Godley & Russell-Mayhew, 2010;Tilden, Eckstrom, & Dieckmann, 2016;Zabar et al, 2016;Zorek et al, 2016), there is no validated quantitative measure of interprofessionalism at the organizational level that is rooted in interprofessional competencies (IPC). Consequently, there is insufficient quantitative evidence to demonstrate that greater organizational IPC leads to better patient health outcomes (Brandt, 2014).…”
Section: Introductionmentioning
confidence: 99%